The problem of modern TV-hero's moral qualities - M. I. Korobko, (Ukrainian Cultural Studies, 2020)
The article is an effort to analyze the image of the modern television hero. Who is he? A hero or a villain? The analysis of modern protagonists is given through ethical and film theories. The problem of clarity of moral boundaries is very important in the light of the trend, which popularizes villains as normal people in modern storytelling, moral boundaries are blurring because of attraction of such heroes. According to Chapman scholars, the functions of modern "bad boy" as an architype are: a) bad boys have the strength to give us freedom at the personal and societal levels; b) a bad boy with a critical view of society can emancipate us on both personal and societal levels; c) bad boy's criticism can lead him to become isolated or withdrawn on a personal level or become a leader of resistance and rebellion on a societal level; d) the comedic bad boy parallels the evils of society and can shed a critical light on what is happening, which in turn can express the need for resistance as well as encourage the individual to retreat from social functions and live in an isolated manner. The complexity of people implies the bad boy limitless in determination because the bad boy appears in many shapes. Many modern heroes in movies and tv-shows are morally ambivalent, they combine features of Hero and Trickster archetypes and become bad boys and girls who question the very essence of our world order. Today there are so many characters like this in mass-culture (tv-series, movies and cartoons) because we live in time of the global world crisis and our culture reflects this, our heroes demonstrate us our problems and try to find a solution. And sometimes the classic understanding of morality can't help us and we are trying to solve the problems through immoral actions. Villains are attractive through their rebellion. Today we can't find clarity of moral boundaries in tv-shows. But it's very important. The influence of series and movies on the young generation is enormous. Cinematography in all forms (cinema and television) is very powerful ethical instrument. And it is not just the mirror of human morality but it has a teaching function too.
Keywords: bad, evil, hero, morality, series, television, villain